Peran orangtua terhadap konsumsi makanan beragam, bergizi, seimbang, dan aman untuk anak usia dini di masa pandemi Covid-19 di Desa Cibojong, Kecamatan Padarincang, Kabupaten Serang, Banten - Nurul Muriyanti; Luluk Asmawati; Laily Rosidah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
This study aims to determine whether or not the influence of the role of parents on B2SA food consumption (diverse, nutritious, balanced, and safe) for early childhood during the COVID-19 pandemic. The subjects in this study were parents who have children aged 5-6 years in Desa Cibojong, Kecamatan Padarincang, Kabupaten Serang-Banten. The method used in this research is using the Ex-post facto method with a quantitative approach. The total population of data in this study amounted to 177 consisting of 5 villages, this sampling technique used the purposive sampling technique while the sample data used in this study amounted to 25 parents who have children aged 5-6 years in Desa Cibojong, Kecamatan Padarincang, Kabupaten Serang-Banten. The data was processed with the help of the IBM SPSS 22.0 for windows program. Based on the results of the study, it can be concluded that there is a significant influence between the role of parents on B2SA food consumption (diverse, nutritious, balanced and safe) for early childhood during the COVID-19 pandemic in Desa Cibojong, Kecamatan Padarincang, Kabupaten Serang-Banten. This can be seen from the significant value obtained at 0.00 < 0.05, which means that Ho is rejected and H1 is accepted.